Heavy metals in agricultural landscapes as hazards to human and ecosystem health: a case study on zinc and cadmium in drainage channel sediments. (15th January 2014) - Savic, Radovan; Ondrasek, Gabrijel; Josimov‐Dundjerski, Jasmina
Abstract BACKGROUND In agricultural systems, heavy metals pose severe risks to the health of soil–plant–animal–human continuum. Drainage channels, as integral components of agricultural landscapes, contain sediment material that can be both a source and a sink of metals and other toxic/persistent elements due to its highly reactive interfaces and strong binding affinity. The drainage channel network in a case study area of Vojvodina (Serbia) is not appropriately protected from contamination, nor is it maintained regularly (e.g. by desilting), thus endangering and potentially decreasing the ecological value of surrounding water and agricultural land resources, i.e. exposing food production to potential contaminants. In this study (2004–2012), Cd and Zn concentrations were analysed in 100 samples from 46 drainage channels sediments spread along the areas of the most intensive agricultural land use in Vojvodina. RESULTS Among the samples measured, 5% had Cd and 14% had Zn concentrations above the maximally permitted levels, indicating that some drainage channel sections have been exposed to different point and non‐point source pollutants. The maximum detected concentrations of the analysed elements were >50% (Zn) and were as much as 11‐fold (Cd) higher than their remediation values. CONCLUSION There is a strong need for the establishment of qualitative monitoring of channel sediment media in agro‐ecosystems closely linked with complex pollution sources (intensive agriculture, industry, urban zones). © 2013 Society of Chemical Industry